Airpolishing effect on bovine enamel and the posterior remineralizing effect of saliva: estudo in vitro Efeito do jato de bicarbonato de sódio sobre o esmalte bovino e posterior efeito remineralizador da saliva - Helena Zaramella Vono Ribeiro; José Eduardo de Oliveira Lima; Bernardo Gonzalez Vono; Maria Aparcida de Andrade Moreira Machado; Salete Moura Bonifácio da Silva (Journal of Applied Oral Science, 2006)
PURPOSE: The aim of the present study was to evaluate the alterations of surface microhardness and wear caused by the sodium bicarbonate jet on bovine enamel and the further remineralizing effect of artificial saliva. METHODS: Fifteen enamel samples (4,0mm x 4,0mm) were used, which constituted the groups: no treatment (MI); treatment with sodium bicarbonate jet (MII and DI); treatment with sodium bicarbonate jet and immersion in saliva for one hour (MIII and DII), 24 hours (MIV and DIII) and 7 days (MV and DIV). Microhardness tests were carried out using a microdurometer in groups M and wear tests by a rugosimeter in groups D. The data were assessed by the one criterion variance analysis and Tukey test. RESULTS: The mean value of microhardness, in KHN, in groups MI, MII, MIII, MIV and MV were 359,80; 335,46; 369,20; 377,73 and 341,86, respectively, whereas the mean values in µm, of wear for group DI, DII, DIII and DIV were 0,564; 0,519; 0,441 and 0,428, respectively. CONCLUSIONS: The sodium bicarbonate jet caused a wear and a reduction in microhardness on the enamel surface; saliva promoted the recovery of initial condition surface microhardness and reduced the wear; the repairing effect of saliva on the surface microhardness alterations occurred within one hour of treatment, having no significant statistical difference from the effect obtained in 24 hours; the best saliva repairing effect on the wear occurred with treatment of 24 hours. OBJETIVO: A finalidade do trabalho foi avaliar as alterações da microdureza e o desgaste provocado pelo jato de bicarbonato de sódio em esmalte bovino e o posterior efeito remineralizador da saliva artificial. MÉTODOS: Utilizaram-se 15 espécimes de esmalte (4,0mm x 4,0mm) que constituíram os grupos: sem tratamento (MI); tratamento com jato de bicarbonato de sódio (MII e DI); tratamento com jato de bicarbonato de sódio e imersão em saliva artificial por uma hora (MIII e DII), 24 horas (MIV e DIII) e sete dias (MV e DIV). Foram realizados testes de microdureza com um microdurômetro nos grupos M e testes de desgaste com um rugosímetro nos grupos D. RESULTADOS: Os dados foram avaliados pela Análise de Variância a um critério e pelo Teste de Tukey. O valor das médias da microdureza, em KHN, nos grupos MI, MII, MIII, MIV e MV foram 359,80; 335,46; 369,20; 377,73 e 341,86; respectivamente, enquanto que os valores médios, em µm, do desgaste para o grupo DI, DII, DIII e DIV foram 0,564; 0,519; 0,441 e 0,428, respectivamente. CONCLUSÕES: o jato de bicarbonato de sódio causou desgaste e diminuição da microdureza superficial; a saliva promoveu o retorno da microdureza superficial à condição inicial e reduziu o desgaste; o efeito reparador da saliva sobre as alterações na microdureza superficial já ocorreu com uma hora de tratamento, não havendo diferença estatisticamente significante do efeito obtido com 24 horas; o melhor efeito reparador da saliva sobre o desgaste ocorreu com 24 horas de tratamento.